APPLICATION OF THE WEIGHTED PRODUCT (WP) METHOD IN DOCTOR PERFORMANCE ASSESSMENT - Zulfan Efendi; Amalia Amalia; Hambali Hambali; Dwi Arisca Pratiwi (STMIK Royal, 2022)
Abstract: In an effort to increase the spirit of better performance and achievement, an institution gives awards to doctors who are considered outstanding. Setia Husodo Hospital is one of the hospitals which is the center of health services in the city of Kisaran. In determining the performance assessment of doctors and leaders, they still use conventional methods. Doctors' performance evaluation is still done manually and the data processing process does not yet use application programs in making decisions. In the process of assessing the performance of doctors as the main professional staff in hospitals, it must be carried out realistically, objectively and based on evidence and specifically according to specialization and/or specific procedures. For this reason, a tool is needed in the form of designing a decision support system (DSS) in evaluating the performance of doctors which aims to understand the deficiencies of the performance that has been carried out, so that it can open up space for improvement or improvements to quality and efficiency in hospitals, for the purpose of providing incentives and reward programs and value-based purchasing strategies for doctors. The method in this study uses the Weighted Product method, with the concept of weighting the rating of an appraisal variable that will be selected as the best alternative. The system to be created is a decision support system using the Weighted Product (WP) method, which is a method of determining the order (priority) in multi-criteria analysis. The results of this system design are expected to be a tool for Setio Husodo Hospital in analyzing and deciding on the performance of doctors who will be given incentives and reward programs as well as value-based purchasing strategies for doctors. Keywords: decision support system; performance of doctors; weighted product; Abstrak: Untuk mendorong kinerja yang lebih baik dan semangat berprestasi, institusi memberikan penghargaan kepada dokter yang dianggap berprestasi.Metode tradisional masih digunakan untuk menilai kinerja dokter dan manajer. Evaluasi kinerja dokter masih bersifat manual, dan proses pengolahan data belum menggunakan program aplikasi untuk mengambil keputusan. Proses evaluasi kinerja dokter sebagai anggota staf rumah sakit penuh waktu harus realistis, objektif, berbasis bukti, dan spesifik untuk spesialisasi dan/atau prosedur tertentu. Oleh karena itu, diperlukan perancangan sistem pendukung keputusan (SPK) untuk evaluasi kinerja dokter sebagai alat yang bertujuan untuk memahami kekurangan dalam pelayanan yang diberikan dan memberikan ruang untuk perbaikan dan ruang untuk peningkatan kualitas dan efisiensi. Rumah sakit mendorong dan memberi dokter program penghargaan dan strategi pembelian berbasis nilai. Metode penelitian ini menggunakan metode weighted product dengan konsep pembobotan evaluasi terhadap satu variabel evaluasi yang dipilih sebagai pilihan terbaik. Sistem yang akan dibuat adalah sistem pendukung keputusan yang menggunakan metode WP (Weighted Product), yaitu metode untuk menentukan urutan (prioritas) dalam analisis multi kriteria. Hasil perancangan sistem ini dimaksudkan sebagai alat bagi RS Setio Husodo untuk menganalisis dan menentukan kinerja dokter penerima program insentif dan reward, serta strategi pembelian berbasis nilai dokter. Kata kunci: kinerja dokter; sistem pendukung keputusan; weighted product